Bioinspired Synthesis of Well‐Ordered Layered Organic–Inorganic Nanohybrids: Mimicking the Natural Processing of Nacre by Mineralization of Block Copolymer Templates. Issue 19 (6th August 2015) - Voet, Vincent S. D.; Kumar, Kamlesh; Brinke, Gerrit ten; Loos, Katja
<x xml:space="preserve">Abstract</x> The unique mechanical performance of nacre, the pearly internal layer of shells, is highly dependent on its complex morphology. Inspired by the structure of nacre, the fabrication of well‐ordered layered inorganic–organic nanohybrids is presented herein. This biomimetic approach includes the use of a block copolymer template, consisting of hydrophobic poly(vinylidene fluoride) (PVDF) lamellae covered with hydrophilic poly(methacrylic acid) (PMAA), to direct silica (SiO2) mineralization. The resulting PVDF/PMAA/SiO2 nanohybrid material resembles biogenic nacre with respect to its well‐ordered and layered nanostructure, alternating organic–inorganic phases, macromolecular template, and mild processing conditions.